2019
DOI: 10.1111/jvh.13093
|View full text |Cite
|
Sign up to set email alerts
|

Advanced liver disease in Russian children and adolescents with chronic hepatitis C

Abstract: Summary Russia has one of the highest prevalences of paediatric chronic hepatitis C infection (CHC). Our aim was to provide a detailed characterization of children and adolescents with CHC including treatment outcomes. Thus, an observational study of children with CHC aged <18 years was conducted in three hepatology centres from November 2014 to May 2017. Of 301 children (52% male), 196 (65%) acquired HCV vertically, 70 (23%) had a history of blood transfusion or invasive procedures, 1 injecting drug use and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
3
9
1
1
Order By: Relevance
“…The discrepancies between the findings of these studies may be due to differences in the age of the participants at the time of enrolment, as well as the causes of liver disease [ 19 ]. Consistent with our findings, the study by Anna et al reported LSM of 5.4 (95% CI 4.0, 7.1) kPa for the F2 stage in children with CHC [ 20 ]. Moreover, a previous study demonstrated that the LSM was able to adequately predict the liver fibrosis stage in adult patients with CHB.…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancies between the findings of these studies may be due to differences in the age of the participants at the time of enrolment, as well as the causes of liver disease [ 19 ]. Consistent with our findings, the study by Anna et al reported LSM of 5.4 (95% CI 4.0, 7.1) kPa for the F2 stage in children with CHC [ 20 ]. Moreover, a previous study demonstrated that the LSM was able to adequately predict the liver fibrosis stage in adult patients with CHB.…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancies between the ndings of these studies may be due to differences in the age of the participants at the time of enrolment and causes of the disease [19]. Consistent with our ndings, the study by Anna et al reported an LSM of 5.4 (4.0, 7.1) kPa for the F2 stage in children with CHC (20). Moreover, a previous study demonstrated that LSM was able to adequately predict the liver brosis stage in adult patients with CHB, and the ROC curves were 0.81 for F0-F1 vs F2-F4 and 0.93 for F0-F2 vs F3-F4 [21], which is consistent with the children with CHB in our study.…”
Section: Discussionsupporting
confidence: 69%
“…(12)(13)(14) The largest TE studies in children with liver disease have examined LSMs in liver transplant recipients (n = 117), cystic fibrosis (n = 249), hepatitis C (n = 223), fatty liver disease (n = 106), and BA (n = 100). (3,(15)(16)(17)(18) These studies correlate LSM with a variety of disease parameters, including clinical features of liver disease, manifestations of portal hypertension, and histologic assessment of fibrosis. The FORCE protocol is unique in that it has been developed in the context of three large-scale, prospective, multicenter, observational studies that collected comprehensive and high-quality clinical metadata in three major etiologies of neonatal cholestasis: BA, ALGS, and A1ATD.…”
Section: Discussionmentioning
confidence: 99%